Cost Comparison of Emergency Cesarean Section in Indonesia: The impact of Australian Model of Diagnosis-related Groups as a Payment System for Patient Care in Hospitals - Rahmawati, Sitti; Graber, Mark A; Hakimi, Mohammad; Multi, Ali Ghufron; Bastian, Indra; Rahman, Nurulhuda (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The cesarean section in Indonesia was higher, still worrying for women and babies’ health with pregnancy complications. It will have psychological effects such as trauma and stress during labor and its consequences on labor cost. AIM: This study’s purpose was to determine the cost of cesarean delivery as a diagnosis of transition-related groups and the Australian-diagnosis-related groups (AR-DRGs) model’s impact. METHODS: The research method is descriptive qualitative study. The 42 samples are pregnant women and that selected by purposive sampling. The data are collected from a secondary data source of medical record installations, observations, interview interviews, and focus group discussion with health professionals, nurses, doctors, and midwives. Data analysis is based on the activity-based costing system method. It includes cost treatment per disease diagnosis, cesarean section AR-DRG 370 method as a payment method for hospital treatment. RESULTS: Determinants of cost differences in cesarean section surgery are based on AR-DRG 370 related to diabetes and eclampsia (complications and comorbidities) with relatively high-cost rates of O01A DRGs of US$ 2639 due to high-risk pregnancy complications. Complications of mild pregnancy (DRGO01D) with different categories of uterine rupture and sepsis have a low-cost average at the total cost of US$ 1251. Payment ability of an average of 42 respondents shows the costs category of DRGs O01A-DRGs O01D US$ 7088 or US$ 169, per patient and length of stay 4–6 days. CONCLUSIONS: The impact of Australia’s AR-DRGs model of transition DRG prospective payment shows that the health system can improve the quality of professional services in hospitals and control costs, and labor costs are cheaply profitable for hospitals. The results are accurate and experienced to be applied in Indonesian hospitals.